Genome-wide characterization of laccase gene family in Schizophyllum commune 20R-7-F01, isolated from deep sediment 2 km below the seafloor - Liu, Xuan; Zain ul Arifeen, Muhammad; Xue, Yarong; Liu, Changhong (Frontiers in Microbiology, 2022)
Laccases are ligninolytic enzymes that play a crucial role in various biological processes of filamentous fungi, including fruiting-body formation and lignin degradation. Lignin degradation is a complex process and its degradation in Schizophyllum commune is greatly affected by the availability of oxygen. Here, a total of six putative laccase genes (ScLAC) were identified from the S. commune 20R-7-F01 genome. These genes, which include three typical Cu-oxidase domains, can be classified into three groups based on phylogenetic analysis. ScLAC showed distinct intron-exon structures and conserved motifs, suggesting the conservation and diversity of ScLAC in gene structures. Additionally, the number and type of cis-acting elements, such as substrate utilization-, stress-, cell division- and transcription activation-related cis-elements, varied between ScLAC genes, suggesting that the transcription of laccase genes in S. commune 20R-7-F01 could be induced by different substrates, stresses or other factors. The SNP analysis of resequencing data demonstrated that the ScLAC of S. commune inhabiting deep subseafloor sediments were significantly different from those of S. commune inhabiting terrestrial environments. Similarly, the large variation of conserved motifs number and arrangement of laccase between subseafloor and terrestrial strains indicated that ScLAC had a diverse structure. The expression of ScLAC5 and ScLAC6 genes was significantly up-regulated in lignin/lignite medium, suggesting that these two laccase genes might be involved in fungal utilization and degradation of lignite and lignin under anaerobic conditions. These findings might help in understanding the function of laccase in white-rot fungi and could provide a scientific basis for further exploring the relationship between the LAC family and anaerobic degradation of lignin by S. commune.